Study on the Scheme of Sensor Arrangement in Pseudo Static Test for Immersed Tunnel Joint. Issue 1 (February 2020) - Cheng, Xinjun; Xu, Kunpeng; Liang, Haian
Abstract: The arrangement scheme of the sensors in a pseudo static test for an immersed tunnel joint was revealed in this paper. To achieve this target, the pushover analysis of the two immersion joint models were studied by using numerical calculation. The mechanical characteristics of the immersed tunnel joint under horizontal loading condition were carefully observed. According to the numerical results, shear keys and connecting part in tunnel elements are the key observation sections, the stress development, the shear capacity and the deformation features of the immersion joint should be measured. Furthermore, a loading system of pseudo static test for immersion joint is also developed. Based on the loading system and numerical funding, the locations for deploying sensors were determined. The scheme of sensor positions played a crucial role in guaranteeing the successful completement of the experiment, and also can offer some reference opinions for similar experiments.